-20 = -4x - 6x-20 = -10x20 = 10x2 = x
-1 + 4x + 6x - 20 =10x - 19
6x - 4y
-20 = -4x - 6x -20 = -10x -20 / -10 = -10x / -10 2 = x x = 2
4x-15=6x-4x 4x-22.4=2x 2x=22.4 x=11.2
-4x-6x = -20 -10x = -20 Divide both sides by -10 rembering that a minus divided into a minus the result is positive: x = 2
-20 = -4x - 6x-20 = -10x20 = 10x2 = x
-1 + 4x + 6x - 20 =10x - 19
6x - 4y
3x - 12 = 10x - 15 - 6x -10 3x - 12 = 4x -25 3x + 13 = 4x 13 = 4x - 3x 13 = x None?
-20 = -4x - 6x -20 = -10x -20 / -10 = -10x / -10 2 = x x = 2
4x-15=6x-4x 4x-22.4=2x 2x=22.4 x=11.2
x = 2
x=2
-4x+3 = 23+6x -4x-6x = 23-3 -10x = 20 x = -2
-20=-4x-6x
-20=-4x-6x -20=-10x {collect like terms} x=2 {divide each side by -10}